Vpliv kompleksantov in proteinov na korozijo nerjavnega jekla in njegovih komponent - Kocijan, Aleksandra (Kovine zlitine tehnologije, 1999)
Our studies are related to the problem of biopdegradation of implants. In vitro simulations of biocompatibility of stainless steel and its components were carried out in simulated physiologic Hank's solution containing different complexing agents and proteins. The concentration of released ions was determined by differential pulse polarography and ICP-AES. The composition of solid corrosion products formed on the surface was analysed by Energy Dispersive Spectroscopy (EDS).
Keywords: nerjavno jeklo; implantati; korozija; kovinski ioni; polarografija; biokompatibilnost